The lexicon of geomorphology. Issue 1 (20th April 2015) - Lewin, John
Abstract: The terms geomorphology uses reveal much about its identity, history, perceptions, external inspirations and methods. Current usage also involves unstated ambiguities. The paper critically reviews the origins, development and nature of the lexicon in English: for discretely identified landforms, for landform sets and hierarchies, and for discussing grand theories. These reflect multiple purposes from the genetically diagnostic to the morphologically descriptive, together with the development of purposeful cognitive and hierarchical classifications, and new terminologies used in the modelling of complex emergent systems. Debate as to the changing and multiple meaning of words is a normal outcome. Metaphors, verbal or otherwise, play a large part in conceptualization. Recent terms relate especially to stimulating technological advances in survey, analysis and modelling. There is now resort to the visual as much as to the verbal for model presentations, together with a much‐increased use of initialisms and similar abbreviated word forms. Copyright © 2015 John Wiley & Sons, Ltd.